UTILIZATION OF ACADEMIC PAPERS IN FORMULATING REGIONAL REGULATIONS IN KUDUS REGENCY - Naili Azizah (Universitas Muhammadiyah Ponorogo, 2020)
This article examines the importance of using academic texts in the preparation ofRegional Regulations and the factors behind the inclusion of academic texts in thepreparation of regional regulations in Kudus district.The Regional Regulations studiedwere the Kudus Regency Regional Regulations in 2015, 2016, 2017, 2018, 2019, and2020.This article is non-doctrinal legal research and is a qualitative descriptive study.The data in this article uses data from in-depth interviews and documentationstudies.From this research, it was found that several factors became the factors for theinclusion of academic texts in the formation of the Kudus Regency Regional RegulationDraft, among others, because in Law Number 12 of 2011 concerning the Formation ofLaws and Regulations - Invitation recommends the inclusion of academic texts in thepreparation of a draft Regulation. Area.Also, the holder of authority from formingregulations who has a background in the field of law, and the involvement of academicswho are involved in helping the process of forming regional regulations in KudusRegency. particularly regarding the formation of laws and regulations is also one of thereasons for the inclusion of academic papers. There are also regional regulations thatdo not make use of academic texts, namely regional regulations on regional budgetsand regional expenditures, regional regulations on accountability for the APBD,regional regulations for amendments, and regional regulations on revocation.